Challenges in a new organization of young employees: issues and interventions - Abdul Wahat, Nor Wahiza; Masdan, Mohd Fauzi (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Organization development is a systematic process to enhance organizational effectiveness through interventions involving technology, individuals and teams in the organization. It involves the design and improvement processes to help individuals, teams and organization function competently and effectively. Schein (1965) suggested two primary elements that must be given full attention by any organization development experts in order to develop successful interventions. First is the adaptability ability of the organization to cope with frequently dynamic changes and second is solid internal integration which allows the organizational components, including the employees, to adapt to changes in the external environment. The paper shall discuss the second element by referring to a case study involving a new organization of young employees. Data were collected via four focus group discussions. The first focus group discussion involved young employees of the organizations. Meanwhile the participants of the fourth focus group discussion were inclusive of the organizational management. Data was then analysed using the constant comparative method. Identified issues and challenges encountered by the new organization in terms of internal integration were (1) ensuring young employees’ understanding of the organizational vision and mission, (2) consolidating the coordination and collaboration among the departments within the organization and (3) cultivating knowledge sharing and learning organization culture among the young employees. Several interventions were recommended based on the findings of the study.